Characterization of extra euchromatic band in the 9qh region - Pangjaidee, Nathaporn; Suphakom, Thongthawee; Luewan, Suchaya; Mevatee, Umnat (Biomedical Sciences and Clinical Medicine, 2024)
Objective The objective of this study was to evaluate the extra G-positive band in the 9qh (9q12) region of two fetuses detected prenatally. Methods Metaphase chromosomes were prepared from fetal blood samplings of two fetuses. G-banding, micro-FISH, mBAND, and FISH techniques were used to evaluate the chromosomal structure of the extra band. Results Chromosome analysis using the G-banding technique revealed an extra G-positive band in the 9qh (9q12) region on one of the chromosomes 9 of both fetuses. The micro-FISH technique showed an extra band in the first case with a similar fluorescent signal to that in band 9q12. The extra band from the mBAND technique revealed a fluorescent signal, and the intensity profile resembled band 9q13. In the second case, the extra band showed no fluorescent signal when it was stained with DAPI and hybridized with labeled human Cot-1 DNA. Both children were born at term with a normal phenotype. Conclusion The extra band in the fi rst case originated from chromosomal material in the 9q12-9q13 region, while that in the second case comprised non-repetitive sequence DNA. The extra band had no clinical effect in either case.